HS-GC-IMS detection of volatile organic compounds in yak milk powder processed by different drying methods. (April 2021) - Feng, Duo; Wang, Jing; Ji, Xiao-jiao; Min, Wen-xiang; Yan, Wen-jie
Abstract: The effects of two drying methods (spray drying, freeze drying) on volatile organic compounds of yak milk powder (YMP) were compared by headspace–gas chromatography–ion mobility spectrometry (HS-GC-IMS) and principal component analysis (PCA). The characteristic fingerprints of YMP after ultra-high pressure sterilization and freeze drying (YMP_UHPS_FD) the YMP after ultra-high pressure sterilization and spray drying (YMP_UHPS_SD), the YMP after thermization and freeze drying (YMP_TH_FD), and the YMP after thermization and spray drying (YMP_TH_SD) were established. In total, 46 signal peaks were identified, and 17 compounds were identified including 6 aldehydes, 5 ketones, 3 acids, 1 terpene, 1 ester and 1 heterocyclic compound. The identified compounds correspond well with the flavors of organic components. In addition, the clustering analysis and fingerprint similarity analysis, based on PCA and Euclidean distance, showed that the similarity of YMP and its corresponding volatile components in different drying methods. The results found that the content of ketones, aldehydes and acids in YMP processed by SD is higher than that of yak milk powder processed by FD, and confirmed that different drying methods confer certain influence on the flavor of YMP, and the results also provide theoretic basis of flavor changes after the deep processing of YMP. Highlights: The yak milk powders were made by spray drying and freeze drying methods. HS-GC-IMS detected yak milk powder' volatile organic compounds. More volatile organic compounds by spraying drying than by freeze drying. PCA and Fingerprint similarity can distinguish different drying yak milk powder.